2019
DOI: 10.3390/bios9040112
|View full text |Cite
|
Sign up to set email alerts
|

Viability of Neural Cells on 3D Printed Graphene Bioelectronics

Abstract: Parkinson’s disease (PD) is the second most common neurodegenerative disease in the United States after Alzheimer’s disease (AD). To help understand the electrophysiology of these diseases, N27 neuronal cells have been used as an in vitro model. In this study, a flexible graphene-based biosensor design is presented. Biocompatible graphene was manufactured using a liquid-phase exfoliation method and bovine serum albumin (BSA) for further exfoliation. Raman spectroscopy results indicated that the graphene produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 82 publications
(102 reference statements)
1
26
0
Order By: Relevance
“…In a recent study, our group observed that rat dopaminergic (N27) neuronal cells live compatibly and adhere to the graphene patterns ( Figure S4) in the biosensing platforms that are made based on the aforementioned methodology [45]. These cells are commonly used in vitro, as models for Parkinson's disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, our group observed that rat dopaminergic (N27) neuronal cells live compatibly and adhere to the graphene patterns ( Figure S4) in the biosensing platforms that are made based on the aforementioned methodology [45]. These cells are commonly used in vitro, as models for Parkinson's disease.…”
Section: Discussionmentioning
confidence: 99%
“…To end with, the resultant conductivity of the printed circuit is characterized, and its stability after submergence in water is exhibited. In another study by our group, the biofunctionalization of the biosensors produced via this process is exhibited [45].…”
Section: Introductionmentioning
confidence: 99%
“…Different studies on IJP with graphene-based inks have been carried out, mainly for applications in electronic, bioelectronic, and energy storage [ 185 , 186 , 187 , 188 , 189 , 190 ]. For example, Li et al reported an easy IJP method for the fabrication of micro-supercapacitors (MSCs) based on graphene and printed on various substrates.…”
Section: Additive Manufacturing For Graphene-based Materialsmentioning
confidence: 99%
“…practical way to stabilize the inks is to use GO or rGO together with surfactants that improve the dispersity of sheets [257,260,261,262], thereby it reduces the probability of agglomerate formation in graphene-based inks [257]. Different studies on IJP with graphene-based inks have been carried out, mainly for applications in electronic, bioelectronic, and energy storage [263][264][265][266][267][268]. For example, in 2017 Li et al [258] reported a simple full-inkjet-printing technique for the scalable fabrication of graphene-based microsupercapacitors (MSCs) on various substrates.…”
Section: Inkjet Printing (Ijp)mentioning
confidence: 99%